Topical treatment with Copaifera langsdorffii oleoresin improves wound healing in rats - Daniela Masson-Meyers; Chukuka Samuel Enwemeka; Violet Bumah; Thiago Andrade; Marco Andrey Frade (International Journal of Phytomedicine, 2013)
Copaifera langsdorffii oleoresin (copaiba) has been used in the Amazon as traditional wound healing remedy for centuries. Since its mechanisms of action remain unclear, we investigated its effects on excisional wounds in rats. Wounds were made on the dorsum of animals assigned to three groups: saline, control cream and 10% copaiba cream, and assessed on days 2, 7 and 14 post-wounding morphometrically, histologically and biochemically. Wound healing rate was faster in copaiba than in saline or cream groups. This was corroborated by matrix metalloproteinase (MMP)-2 activity which rose progressively throughout in copaiba group. MMP-9, a marker of inflammation, was not detectable at day 14 in copaiba group, but persisted in the other groups. Moreover, histology showed early population of copaiba-treated wounds by inflammatory cells, and by day 14 this group had less fibroblasts and more organized collagen. Further, copaiba group synthesized collagen faster than saline and cream groups, as evidenced by progressive increases in the amounts of hydroxyproline at days 7 and 14 (p < 0.012). These findings suggest that 10% copaiba oleoresin cream promotes wound healing in rats by regulating MMP-2 and MMP-9 activities, stimulating collagen synthesis and promoting tissue remodeling and reepithelialization.